2017
DOI: 10.1007/s41024-016-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical assessment of night ventilation impact on the thermal comfort of vernacular buildings

Abstract: Night ventilation, is one of the most effective passive cooling techniques that may contribute to the improvement of the occupants thermal comfort conditions. Despite the justified effectiveness of night ventilation, few studies quantified its influence on the thermal comfort of vernacular buildings, especially under warm dominant climates. The aim of this study is the investigation of the impact of night ventilation on the thermal comfort of vernacular buildings under summer dominant environmental conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Their findings showed the possibility of eliminating air-conditioning during the full working period, and depending on which category of comfort is set, the temperature reduction averages 1 °C. The impact of NV on improving internal thermal comfort levels was studied by Exizidou et al [17]. The outcomes of the study demonstrate that the average PMV index for the non-ventilated and night ventilated zones was 2.25 and 1.1 respectively.…”
Section: Natural Cooling (Cross and Stack Driven Air-flow)mentioning
confidence: 95%
See 2 more Smart Citations
“…Their findings showed the possibility of eliminating air-conditioning during the full working period, and depending on which category of comfort is set, the temperature reduction averages 1 °C. The impact of NV on improving internal thermal comfort levels was studied by Exizidou et al [17]. The outcomes of the study demonstrate that the average PMV index for the non-ventilated and night ventilated zones was 2.25 and 1.1 respectively.…”
Section: Natural Cooling (Cross and Stack Driven Air-flow)mentioning
confidence: 95%
“…Al-Ain city, United Arab Emirates (BWh) Low-Rise heavy residential buildings Improving NV with a combined wallroof solar chimney [31,32] A full-scale model (EnergyPlus) derived form an experimental model in Arizona [33] Yazd, Iran (BWh) A typical office building with lightweight structure Combined use of PCMs to optimise NV [17] Simulations of EnergyPlus and the flow solver of Design Builder Nicosia, Cyprus (BSh) Vernacular buildings…”
Section: Utilization Of Night Ventilation In Different Climatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, through climate modeling over the last decade, it's been demonstrated that the temperature has risen by 1 to 3 C⁰ and it's estimated that by the end of the century, the yearly period of high temperatures (excess of 38 C⁰), i.e. the summer season, will last an additional 2 months, resembling the conditions in cities like Cairo and Bahrain (Exizidou et al, 2017). These temperature fluctuations of cooler nights (25 C⁰) and warmer days showcase a magnitude of difference of around 15 C⁰, that can lead to an excessive rate of deterioration of facades due to the higher thermal stresses developed in the materials (Christoudias et al, 2012).…”
Section: Temperature Fluctuationsmentioning
confidence: 99%
“…The indoor temperature reduction effect by night ventilation is significantly affected by the heat capacity of the building, the amount of ventilation, and the change in outdoor temperature [6]. Exizidou et al [7] found that thermal comfort levels improved by an average of 26% with the use of night ventilation in vernacular buildings. Geros et al [8] presented the key parameters, which include the effective night-time airflow rate, as well as the indoor-outdoor temperature differential.…”
Section: Introduction 1backgroundmentioning
confidence: 99%